Kewenangan Penyidik Pegawai Negeri Sipil dalam Penanganan Tindak Pidana Karantina Ikan Berdasarkan Ketentuan Undang-Undang Nomor 21 Tahun 2019 - Ichsan, Muhammad Nur; Asis, Abd.; Mirzana, Hijrah Adhyanti (Universitas Negeri Malang, 2022)
This study aimed to analyze the implementation of the authority of civil servant investigators and analyze the inhibiting factors for civil servant investigators to handle fish quarantine crimes. This study used an empirical juridical method with a sociological juridical approach. Civil servant investigators' authority to handle fish quarantine crimes was carried out based on Article 83 paragraph (2) of Law Number 21 of 2019 through coordination with the police, which includes two fields, namely the field of guidance and operations. The inhibiting factors for civil servant investigators in handling fish quarantine crimes were divided into law enforcement factors and legal substances.